Estudo das percepções dos coordenadores pedagógicos e dos alunos sobre orientação profissional em escolas de ensino médio no município de Araguaína - TO. - Leite, Fabiola de Sousa (Universidade Federal do Tocantins, 2023)
This study describes policies and actions of professional orientation at Centro de Ensino Médio (CEM) Paulo Freire and Instituto Federal do Tocantins (IFTO) in Araguaína (TO) according to students and education directors of these two institutions. This work was conducted in two steps using questionnaires in both cases. In the first step, students between 15 and 19 years old reported the influence of their relatives in the carreer they are choosing. They also showed their anxiety and expectations about a future career. In the second step, education directors of the schools presented professional orientation policies of their institutions. Results showed that students fear to make the wrong decision concerning their future career. They fear waste time in this process. The research also showed the importance of identifying the origin of the disappointments of the students and presented the need of a more efficient policy of professional guidance before students enter to college.